Preliminary investigations of in vitro antioxidant, antityrosinase, acetylcholinesterase and anti-inflammatory activities of Actinodaphne species antikolinesteraz ve antienflamatuvar etkilerinin arastirilmasi - Wan Salleh, Wan Mohd. Nuzul Hakimi (Marmara University, 2016)
The purpose of this study was to investigate the biological activities of extracts from two Actinodaphne species from Malaysia, which are Actinodaphne macrophylla and Actinodaphne pruinosa. The in vitro activity studies were assessed for their antioxidant, antityrosinase, acetylcholinesterase and anti-inflammatory activities. The methanolic bark extract of A. pruinosa have shown the highest activity on DPPH· (IC50: 70.2 μg/mL), ABTS·+ (IC50: 147.2 μg/mL) and phenolic content (55.1 mg gallic acid/g), while the bark extracts of A. macrophylla showed the best inhibitory activity against mushroom tyrosinase (I: 45.2%) and lipoxygenase (I: 69.2%) assays. All extracts have shown strong AChE inhibitory activity (I: 70.5–88.1%), comparable to galantamine (I: 95.9%). The isolation of specific bioactive compounds as well as evaluating their safety may be necessary in the exploration of these species for potential new therapeutic drugs or drug leads.